FACTORS INFLUENCING THE DECISION TO PURCHASE PET INSURANCE IN BANGKOK METROPOLIS AND VICINITY - Wiriyaphol, Wipawinee; Sukpaiboonwat, Sivalap (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
The purpose of this research is to study and analyze the factors influencing the decision to purchase pet insurance in the Bangkok metropolis and vicinity. The study examines personal factors, pet information, marketing mix factors from the producer's perspective (7Ps), and marketing mix factors from the consumer's perspective (7Cs). The sample used in the research consisted of a total of 420 dog and cat owners, with data collected through online questionnaires. The data were analyzed using Binary Choice Models, specifically Logit Models. The study found that personal factors, such as monthly income, significantly influence the decision to purchase pet insurance. An increase of one unit in monthly income raises the probability of deciding to buy pet insurance by 3%. Pet-related factors, such as the price of the pet, also play a role, with a one-unit increase in pet price raising the probability of purchasing pet insurance by 2.5%. From the producer's perspective, marketing mix factors (7Ps), such as the service process, are critical. A faster and more appropriate claim processing time increases the likelihood of purchasing pet insurance by 4.8%. From the consumer's perspective, marketing mix factors (7Cs) also significantly influence the decision. The most important thing pet owners value is the care and attention of the employees, with a one-unit increase in the employee's ability to quickly give advice raising the probability of purchasing pet insurance by 4.4%, which is statistically significant at the 95 percent confidence level. This research identifies factors influencing the decision to purchase pet insurance, which can be used to provide recommendations to relevant private sector organizations. Owners' income, pet prices, and insurance company services, including speed of medical bill payment, employee care, which increase the chance of deciding to buy pet insurance. Therefore, marketing efforts should be targeted at groups with these characteristics. This information can be used to further develop and improve the private insurance sector by creating insurance plans and services that better align with consumer needs.